Decoding eQTLs: unraveling their role in spondyloarthropathies pathogenesis and potential therapeutics - Awadh, Nabaa Ihsan; Ridha, Asal Adnan; Younus, Marwah Muayad; Humadi, Yasameen Abbas; Gorial, Faiq I.; Khalid, Khalid Burhan; Rasool, Yousif Alaa (Frontiers in Immunology, 2025)
Expression quantitative trait loci (eQTLs) represent genetic variants that influence gene expression, providing insights into the mechanisms linking genetic predisposition to complex diseases, including spondyloarthropathies (SpAs). SpAs, encompassing ankylosing spondylitis, psoriatic arthritis, reactive arthritis, and enteropathic arthritis, are related heterogeneous conditions with strong genetic components, particularly in HLA-B27 and non-HLA loci, but phenotypically distinct disorders. Recent advances in genome-wide association studies (GWAS) and transcriptomic studies have shown the potential of such eQTLs to provide insights into the disease biology, delineate potential drug targets, and enable precision medicine. This mini-review provides a comprehensive overview of eQTLs—discovery, definition, and functional implication into eQTLs gene regulation. We review their role in SpA pathogenesis, controversy and methodological issues in eQTL studies, literature gaps, and directions for the future. By combining genetic, immunological, and computational information, we aim to present an unbiased perspective on the role of eQTLs in advancing SpA research and treatment.